1996
DOI: 10.1159/000109177
|View full text |Cite
|
Sign up to set email alerts
|

Activin and Follistatin as Local Regulators in the Human Ovary

Abstract: There is increasing evidence that activin may act as an autocrine/paracrine regulator of ovarian functions. Activin subunit mRNAs as well as activin immunoreactivities have been detected in the human ovary. Activin alters granulosa cell proliferation and steroidogenesis. The effect of activin is most likely mediated through specific receptors as mRNAs encoding several forms of activin receptors, namely ActR-I, ActR-IB, ActR-II and ActR-IIB are found in the preovulatory follicles as well as in cultured granulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The activin-A protein was previously demonstrated in rat (Ogawa et al, 1991) and human (Rabinovici et al, 1992;Wada et al, 1996) corpora lutea. The mRNA of activin receptor type II was detected in rat (Cameron et al, 1994) and human (Peng et al, 1996) luteal tissue. In the current study with pregnant pigs, we also found activin gene expression, activin protein, and activin receptor type II in corpora lutea and, moreover, in the ovarian surface epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The activin-A protein was previously demonstrated in rat (Ogawa et al, 1991) and human (Rabinovici et al, 1992;Wada et al, 1996) corpora lutea. The mRNA of activin receptor type II was detected in rat (Cameron et al, 1994) and human (Peng et al, 1996) luteal tissue. In the current study with pregnant pigs, we also found activin gene expression, activin protein, and activin receptor type II in corpora lutea and, moreover, in the ovarian surface epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Both inhibin and activin have been reported to modulate steroidogenesis, including progesterone production, in mammals [5,59,60]. It is possible that activin A and inhibin A may stimulate MIH production, which in turn, induces oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…FST exerts its effect via enhancement of estradiol production in addition to neutralizing the effect of activin on steroid production [25]. …”
Section: Discussionmentioning
confidence: 99%